Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Minat Beli Melalui Kepuasan Konumen - Rahma Sinurat; Deka Wulandari; Elza Nitami Harahap; Mutiara Syahna (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2023)
Purchase interest has a good influence on sellers and entrepreneurs. Researchers have carried out many tests on how to increase buying interest among the public. From this research, we aim to find out whether buying interest will have the influence of good service quality and appropriate product quality which will make consumers feel satisfied which will result in repeat buying interest. With an infinite population, researchers had to use purposive sampling for sampling and obtained 30 samples. In analyzing the hypothesis using SEM-PLS calculations in the SmartPLS application. From the test results it was found that the influence of service quality on buying interest was significant, whereas for product quality and testing the 3 variables together produced values that had no effect on buying interest. This research can helps sellers and entrepreneurs in increasing buying interest among the public. The high level of competition in increasing sales means sellers have to think about attracting consumers. Improving the quality of service can be an initial step in making people interested in buying at the Sukaramai market in Medan.